Brief daily functional strength training to improve functional performance in older adults with mobility disability: A randomized trial - Smita Dandekar; Jordan Kurth; Yimeng Shang; Jonathan G. Stine; Matthew A. Ladwig; David E. Conroy; Kathryn H. Schmitz; Liza S. Rovniak; Matthew Silvis; Margaret Danilovich; Noel Ballentine; Natalia Pierwola-Gawin; et al. (PLoS ONE, 2026)
Objectives Mobility disability is associated with functional decline in older adults. Resistance training (RT) improves mobility disability, but adherence to national RT guidelines is poor. We evaluated the effects of a 12-week brief, home-based functional RT program, FAST ( Functional Activity Strength Training) -2, on adherence and functional impairment in older, inactive adults ≥ 65 years of age, with pre-existing walking difficulty. Methods Eligible older adults were randomized using stratified assignment based on biological sex and age (65−72 and 73+) to either the FAST-2 intervention involving a 4-minute daily workout of four exercises lasting 30 seconds each or the delayed treatment control condition. Video coaching at baseline and at weeks 2, 4 and 8, provided feedback on exercise form, modifications and progression. Daily email reminders were sent for workout completion, and to report exercise performance and rate perceived exertion. Performance and adherence feedback were emailed biweekly. Functional performance was measured by video using the Five-Times Sit-to-Stand (FTSTS) test, One-Legged Stance Test (OLST) and the 30-second chair stand test at baseline and at weeks 6 and 12. Results Ninety-seven participants were randomized to either the FAST-2 treatment intervention (n = 44) or the delayed treatment control condition (n = 53). The linear mixed-effect model showed the intervention group decreased the FTSTS by 2.3 seconds (95% CI: 0.5–4.1, p = 0.01), increased OLST by 3.6 seconds (95% CI: 0.6–6.5, p = 0.02) and increased the number of chair stands by 4.2 repetitions (95% CI: 2.8–5.7, p < 0.001) more than the control group over 12 weeks. Intervention participants completed the workout 81% of the days. No significant adverse events were reported. Conclusion The 12-week FAST-2 intervention, including only 60-seconds of lower extremity exercises in older individuals with pre-existing walking difficulty, yielded improvement in functional performance. Trial registration ClinicalTrials.gov: ID NCT05697497 Study Details | NCT05697497 | Functional Activity Strength Training | ClinicalTrials.gov